PECVD (Plasma Enhanced Chemical Vapor Deposition) preparation process of optical thin film and optical thin film prepared by
Through the PECVD process of multi-layer film structure with specific sequence and thickness, the problem of insufficient stress and binding force between the film layers is solved, and the preparation of high-performance optical films is realized, with excellent transmittance and long life.
Patent Information
- Application Number
- CN202411677512.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-11-22
AI Technical Summary
When the existing PECVD technology deposits multilayer film structures, the internal stress between the film layers is large and the binding force is not high, which limits its application in the preparation of high-performance optical films.
The PECVD preparation process of SiOx layer, SiNx layer, SiOxNy layer, and SiOxFy layer with specific order arrangement and thickness is adopted to reduce reflectivity through interference cancellation, and improve the adhesion fastness between the film layers through substrate preheating and transition layers to control Gas flow rate and radio frequency power to improve bond fastness and stability of the film layer.
The excellent transmittance of the optical film in the wavelength range of 450-530 nm, 600-700 nm and 1000-1200 nm is achieved, and the bonding fastness and stability between the film layers are improved, and the service life of the optical film is extended.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the field of optical film preparation, and in particular to a PECVD preparation process for an optical film and the optical film prepared therefrom. Background Art
[0002] Optical thin films are widely used in various optical systems to adjust the transmission characteristics of light. At present, the traditional methods for preparing optical thin films mainly include evaporation, sputtering, physical vapor deposition, chemical vapor deposition, and plasma enhanced chemical vapor deposition (PECVD). These methods have their own advantages, but also have some limitations.
[0003] Among them, plasma enhanced chemical vapor deposition (PECVD) has been widely used in the field of optical thin film preparation due to its advantages such as fast deposition speed and strong controllability. However, the existing PECVD technology still has problems such as large internal stress between film layers and low bonding strength when depositing multi-layer film structures, which limits its application in the preparation of high-performance optical films. Summary of the invention
[0004] In order to improve the problems of large internal stress and low bonding strength between multilayer optical films in the related art, the present application provides a PECVD preparation process for an optical film and the optical film prepared therefrom.
[0005] In the first aspect, the PECVD preparation process of an optical film provided in the present application adopts the following technical solution: A PECVD preparation process for an optical film comprises the following steps: S1. Preheating the substrate: Preheat the double-sided polished substrate in a vacuum of 3.5*10 -4 Pa-4.0*10 -4 Pa, preheat in a chamber at 100-105°C for 10-20 min; S2, deposition of SiO x Layer: Stop evacuating the chamber, introduce SiH4 and N2O into the chamber, the flow ratio of SiH4 to N2O is 1:(1.0-1.2), the RF power is controlled to 200-250W, the reaction pressure is controlled to 20-30Pa, and the deposition thickness is 25-35nm; S3, deposition of SiN x Layer: Evacuate the chamber to 9.4*10 -3 Pa-9.8*10 -3 Pa, then stop vacuuming, introduce SiH4 and N2 into the chamber, the flow ratio of SiH4 to N2 is 1: (1.0-1.2), the RF power is controlled to 200-250W, the reaction pressure is controlled to 20-30Pa, and the deposition thickness is 10-15nm; S4, deposition of SiO x N y Layer: Evacuate the chamber to 9.4*10 -3 Pa-9.8*10 -3 Pa, then stop vacuuming, introduce SiH4, N2O and N2 into the chamber, the flow ratio of SiH4, N2O and N2 is (4-8): 1: (4-8), the RF power is controlled to 200-250W, the reaction pressure is controlled to 20-30Pa, and the deposition thickness is 135-155nm; S5. Deposition of SiO x F y Layer: Evacuate the chamber to 9.4*10 -3 Pa-9.8*10 -3 Pa, then stop vacuuming, and introduce SiH4, N2O and C2F6 into the chamber. The flow ratio of SiH4, N2O and C2F6 is (4-8): (4-8): 1, the RF power is controlled to 200-250W, the reaction pressure is controlled to 20-30Pa, and the deposition thickness is 80-90nm; S6, repeat steps S4 and S5 3-8 times in sequence; S7. Repeat steps S2 and S3 once to obtain an optical film.
[0006] In this application, the SiO x Layer, SiN x Layer, SiO x N y Layer, SiO x F y The optical film has excellent transmittance in the wavelength ranges of 450-530nm, 600-700nm and 1000-1200nm. In addition, the internal stress between the film layers of the optical film of the present application is small and the bonding strength is high, which can effectively improve the overall bonding strength and stability of the optical film and extend the service life of the optical film.
[0007] Among them, the substrate is first polished and preheated to provide a good foundation for the deposition of subsequent film layers, which is beneficial to improving the bonding strength between the film layer and the substrate, thereby improving the overall stability of the optical film.
[0008] Pre-deposit SiO on the substrate x layer, as a substrate with SiN x The transition layer between layers can improve the SiN xThe stress difference between the layer and the substrate prevents the film layer from cracking and peeling due to excessive stress. It is also beneficial to improve the adhesion between the film layers, thereby enhancing the overall stability of the optical film.
[0009] At the same time, through the coordination of the coating parameters of each film layer, the reflectivity of the optical film can be reduced, the transmittance of the optical film in the wavelength range of 450-530nm, 600-700nm and 1000-1200nm can be increased, and the internal stress between the film layers can be effectively reduced, thereby improving the overall bonding strength and stability of the optical film, which is conducive to obtaining an optical film that takes into account both optical performance and stability.
[0010] SiN x As the surface layer of the optical film, SiN x It has excellent hardness and wear resistance, which can effectively prevent scratches on optical films and help extend the service life of optical films.
[0011] In some specific embodiments, the deposited SiO x N y When the layer is formed, the flow ratio of SiH4, N2O and N2 is (5-5.5):1:(4.2-4.5).
[0012] In this application, the deposited SiO x N y When forming the optical film, the flow ratio of SiH4, N2O and N2 is further preferably (5-5.5):1:(4.2-4.5), which is beneficial to further improve the transmittance of the optical film in the wavelength range of 450-530nm, and at the same time is beneficial to further improve the thickness uniformity of the optical film.
[0013] In some specific embodiments, the deposited SiO x F y When the layer is formed, the flow ratio of SiH4, N2O and C2F6 is (5-5.5): (4.8-5.2):1.
[0014] In this application, the deposited SiO x F y When forming the optical film, the flow ratio of SiH4, N2O and C2F6 is further preferably (5-5.5): (4.8-5.2): 1, which is beneficial to further improve the transmittance of the optical film in the wavelength range of 450-530nm, and at the same time is beneficial to further improve the thickness uniformity of the optical film.
[0015] In some specific embodiments, in step S2, the flow rate of SiH4 is controlled to be 70-75 sccm, in step S3, the flow rate of SiH4 is controlled to be 70-75 sccm, in step S4, the flow rate of N2O is controlled to be 15-20 sccm, and in step S5, the flow rate of C2F6 is controlled to be 15-20 sccm.
[0016] In the present application, by controlling the gas flow rate in each step within the above range, it is possible to achieve a faster deposition rate while ensuring the deposition flatness of each film layer and the bonding strength between the film layers, which is beneficial to improving the thickness uniformity and structural stability of the optical film.
[0017] In some specific embodiments, in step S6, steps S4 and S5 are repeated 4-5 times in sequence.
[0018] In the present application, when steps S4 and S5 are repeated 4-5 times in sequence, the transmittance of the obtained optical film in the wavelength ranges of 450-530nm, 600-700nm and 1000-1200nm is more than 90%, and the optical performance of the optical film is further improved.
[0019] In some specific embodiments, the SiO x The layer was deposited with a thickness of 28-30 nm.
[0020] In the present application, SiO x The deposition thickness of the layer is 28-30nm, which can further reduce the SiN x layer and substrate or SiO x F y The stress between the layers can be reduced, thereby further improving the bonding strength between the optical film layers.
[0021] In some specific embodiments, the SiN x The layer was deposited with a thickness of 10-12 nm.
[0022] In the present application, SiN is further preferred. x The deposition thickness of the layer is 10-12 nm, which can obtain a scratch-resistant optical film while obtaining an optical film with good light transmittance.
[0023] In some specific embodiments, the SiO x N y The deposition thickness of the layer is 140-145 nm. x F y The deposited layer thickness was 84.5-86.5 nm.
[0024] In the present application, SiO xN y The deposition thickness of the layer is 140-145nm, SiO x F y The deposition thickness of the layer is 84.5-86.5 nm, which is beneficial to further improve the transmittance of the optical film in the wavelength ranges of 450-530 nm, 600-700 nm and 1000-1200 nm.
[0025] In some specific embodiments, the substrate is any one of a polymethyl methacrylate substrate, a polycarbonate substrate, and a polystyrene substrate.
[0026] In a second aspect, the present application provides an optical film produced by the PECVD preparation process of any of the above-mentioned optical films.
[0027] In summary, this application at least includes the following beneficial technical effects: (1) In this application, SiO2 is arranged in a specific order and with a specific thickness. x Layer, SiN x Layer, SiO x N y Layer, SiO x F y The optical film has excellent transmittance in the wavelength ranges of 450-530nm, 600-700nm and 1000-1200nm. In addition, the internal stress between the film layers of the optical film of the present application is small and the bonding strength is high, which can effectively improve the overall bonding strength and stability of the optical film and extend the service life of the optical film.
[0028] (2) In the present application, when steps S4 and S5 are repeated 4-5 times in sequence, the transmittance of the obtained optical film in the wavelength ranges of 450-530nm, 600-700nm and 1000-1200nm is more than 90%, and the optical performance of the optical film is further improved. DETAILED DESCRIPTION
[0029] The present application is further described below in conjunction with specific experiments. The optical films in the embodiments and comparative examples of the present application are prepared using a PECVD-1201 plasma enhanced chemical vapor deposition system, but are not limited to this equipment. Example
[0030] [Example 1] An optical film is prepared by a PECVD preparation process. The specific PECVD preparation process includes the following steps: S1. Preheating the substrate: Preheat the double-sided polished polymethyl methacrylate substrate in a vacuum of 3.5*10 -4 Pa, preheated in a chamber at 100°C for 20 min; S2, deposition of SiO x Layer: stop evacuating the chamber, introduce SiH4 and N2O into the chamber, the flow rate of SiH4 is controlled to 45sccm, the flow ratio of SiH4 to N2O is 1:1, the RF power is controlled to 200W, the reaction pressure is controlled to 30Pa, and the deposition thickness is 25nm; S3, deposition of SiN x Layer: Evacuate the chamber to 9.4*10 -3 Pa, then stop vacuuming, introduce SiH4 and N2 into the chamber, the flow rate of SiH4 is controlled to 45sccm, the flow ratio of SiH4 to N2 is 1:1, the RF power is controlled to 200W, the reaction pressure is controlled to 30Pa, and the deposition thickness is 10nm; S4, deposition of SiO x N y Layer: Evacuate the chamber to 9.4*10 -3 Pa, then stop vacuuming, introduce SiH4, N2O and N2 into the chamber, the flow rate of N2O is controlled to 10sccm, the flow ratio of SiH4, N2O and N2 is 4:1:4, the RF power is controlled to 200W, the reaction pressure is controlled to 30Pa, and the deposition thickness is 135nm; S5. Deposition of SiO x F y Layer: Evacuate the chamber to 9.4*10 -3 Pa, then stop vacuuming, introduce SiH4, N2O and C2F6 into the chamber, the flow rate of C2F6 is controlled to 10sccm, the flow ratio of SiH4, N2O and C2F6 is 4:4:1, the RF power is controlled to 200W, the reaction pressure is controlled to 30Pa, and the deposition thickness is 80nm; S6, repeat steps S4 and S5 three times in sequence; S7. Repeat steps S2 and S3 once to obtain an optical film.
[0031] [Example 2] An optical film is prepared by a PECVD preparation process. The specific PECVD preparation process includes the following steps: S1. Preheating the substrate: Preheat the double-sided polished polymethyl methacrylate substrate in a vacuum of 4.0*10 -4 Pa, preheat in a chamber at 105°C for 10 min; S2, deposition of SiO xLayer: stop evacuating the chamber, introduce SiH4 and N2O into the chamber, the flow rate of SiH4 is controlled to 45sccm, the flow ratio of SiH4 to N2O is 1:1.2, the RF power is controlled to 250W, the reaction pressure is controlled to 20Pa, and the deposition thickness is 35nm; S3, deposition of SiN x Layer: Evacuate the chamber to 9.8*10 -3 Pa, then stop vacuuming, introduce SiH4 and N2 into the chamber, the flow rate of SiH4 is controlled to 45sccm, the flow ratio of SiH4 to N2 is 1:1.2, the RF power is controlled to 250W, the reaction pressure is controlled to 20Pa, and the deposition thickness is 15nm; S4, deposition of SiO x N y Layer: Evacuate the chamber to 9.8*10 -3 Pa, then stop vacuuming, introduce SiH4, N2O and N2 into the chamber, the flow rate of N2O is controlled to 10sccm, the flow ratio of SiH4, N2O and N2 is 8:1:8, the RF power is controlled to 250W, the reaction pressure is controlled to 20Pa, and the deposition thickness is 155nm; S5. Deposition of SiO x F y Layer: Evacuate the chamber to 9.8*10 -3 Pa, then stop vacuuming, introduce SiH4, N2O and C2F6 into the chamber, the flow rate of C2F6 is controlled to 10sccm, the flow ratio of SiH4, N2O and C2F6 is 8:8:1, the RF power is controlled to 250W, the reaction pressure is controlled to 20Pa, and the deposition thickness is 90nm; S6, repeat steps S4 and S5 8 times in sequence; S7. Repeat steps S2 and S3 once to obtain an optical film.
[0032] [Example 3] An optical film, which differs from [Example 1] in that: in step S4, the flow ratio of SiH4, N2O and N2 is 5:1:4.5.
[0033] [Example 4] An optical film, which differs from [Example 1] in that: in step S4, the flow ratio of SiH4, N2O and N2 is 8:1:8.
[0034] [Example 5] An optical film, which differs from [Example 3] in that: in step S5, the flow ratio of SiH4, N2O and C2F6 is 5:5:1.
[0035] [Example 6] An optical film, which differs from [Example 3] in that: in step S5, the flow ratio of SiH4, N2O and C2F6 is 8:8:1.
[0036] [Example 7] An optical film, which differs from [Example 5] in that: in step S2, the flow rate of SiH4 is controlled to 70sccm, in step S3, the flow rate of SiH4 is controlled to 70sccm, in step S4, the flow rate of N2O is controlled to 18sccm, and in step S5, the flow rate of C2F6 is controlled to 18sccm.
[0037] [Example 8] An optical film, which differs from [Example 5] in that: in step S2, the flow rate of SiH4 is controlled to 85sccm, in step S3, the flow rate of SiH4 is controlled to 85sccm, in step S4, the flow rate of N2O is controlled to 25sccm, and in step S5, the flow rate of C2F6 is controlled to 25sccm.
[0038] [Example 9] An optical film, which differs from [Example 7] in that: in step S6, steps S4 and S5 are repeated five times in sequence.
[0039] [Example 10] An optical film, which differs from [Example 7] in that: in step S6, steps S4 and S5 are repeated 8 times in sequence.
[0040] [Example 11] An optical film, which differs from [Example 9] in that: SiO x The deposition thickness of the layer is 30nm, SiN x The deposition thickness of the layer is 10 nm, SiO x N y The deposition thickness of the layer is 142nm, SiO x F y The deposited layer thickness was 85 nm.
[0041] [Example 12] An optical film, which differs from [Example 9] in that: SiO x The deposition thickness of the layer is 35nm, SiN x The deposition thickness of the layer is 15 nm, SiO x N y The deposition thickness of the layer is 155nm, SiO x F y The layer was deposited with a thickness of 90 nm.
[0042] Comparative Example [Comparative Example 1] An optical film, which differs from [Example 1] in that step S6 is omitted.
[0043] [Comparative Example 2] An optical film, which differs from [Example 1] in that: in step S6, steps S4 and S5 are repeated 10 times in sequence.
[0044] [Comparative Example 3] An optical film, which differs from [Example 1] in that: the substrate and the SiN x SiO between layers x layer.
[0045] Performance testing (1) Transmittance: The transmittance of the optical film in each embodiment and comparative example within the wavelength ranges of 450-530 nm, 600-700 nm and 1000-1200 nm was tested, and the minimum and maximum values of the transmittance within each wavelength range were recorded.
[0046] (2) Thickness non-uniformity: The optical films in the embodiments and comparative examples were cut into samples with a size of 200 mm*200 mm*200 mm. The thickness was tested at 9 locations on the samples at equal intervals. The thickness non-uniformity of the optical films was calculated. Thickness non-uniformity = (d max -d min ) / d avg , in this formula, d max represents the maximum thickness in the sample, d min represents the minimum thickness in the sample, d avg Represents the average thickness of 9 locations. The smaller the thickness non-uniformity, the better the thickness uniformity of the optical film.
[0047] (3) Film bonding strength: The test was conducted in accordance with Section 7 of GB / T 26332.4-2015. The tape was pulled up at a rate of 30 mm / s. The adhesion grade of the film was recorded according to the evaluation system in the standard. The lower the adhesion grade, the higher the bonding strength between the film layers.
[0048] Table 1 Light transmittance record table
[0049] Table 2 Thickness non-uniformity and adhesion level record table
[0050] The difference between Comparative Examples 1 and 2 and Example 1 is that: SiO x Ny Layer, SiO x F y The number of layers is different. Among them, in Comparative Example 1, SiO x N y Layer, SiO x F y The number of layers is 1 layer each, and in Comparative Example 2, SiO x N y Layer, SiO x F y The number of layers is 11, and in Example 1, SiO x N y Layer, SiO x F y The number of layers is 4, that is, SSiO x N y Layer, SiO x F y The number of layers is within the range of 4-9 layers defined in the present application. The SiO x N y Layer, SiO x F y The number of layers is not within the range defined in the present application. Combining the test data in Table 1-2, it can be seen that the thickness uniformity and the adhesion strength between the film layers of the optical film in Comparative Example 1-2 are comparable to those of Example 1, but the transmittance of the optical film in Comparative Example 1-2 in the wavelength ranges of 450-530nm, 600-700nm and 1000-1200nm are all reduced.
[0051] The difference between Comparative Example 3 and Example 1 is that: Comparative Example 3 omits the x SiO between layers x Combined with the test data in Table 1-2, it can be seen that omitting SiO x After the coating, the transmittance of the optical film in the wavelength ranges of 450-530nm, 600-700nm and 1000-1200nm decreased. At the same time, the adhesion level between the optical film layers increased, indicating that the bonding strength between the film layers decreased.
[0052] The difference between Example 3-4 and Example 1 is that in step S4 of Example 3, the flow ratio of SiH4, N2O and N2 is in the range of (5-5.5):1:(4.2-4.5). Combining the data in Table 1-2, it can be seen that the flow ratio of SiH4, N2O and N2 is in the range of (5-5.5):1:(4.2-4.5), which is conducive to further improving the transmittance of the optical film in the wavelength range of 450-530nm.
[0053] The difference between Example 5-6 and Example 3 is that in step S5 of Example 5, the flow ratio of SiH4, N2O and C2F6 is in the range of (5-5.5): (4.8-5.2): 1. Combined with the detection data in Table 1-2, it can be seen that the flow ratio of SiH4, N2O and C2F6 is in the range of (5-5.5): (4.8-5.2): 1, which is conducive to further improving the transmittance of the optical film in the wavelength range of 450-530nm.
[0054] The difference between Example 7-8 and Example 5 is that in Example 7, the flow rate of SiH4 is controlled within the range of 70-75 sccm, in step S3, the flow rate of SiH4 is controlled within the range of 70-75 sccm, in step S4, the flow rate of N2O is controlled within the range of 15-20 sccm, and in step S5, the flow rate of C2F6 is controlled within the range of 15-20 sccm. Combining the detection data in Table 1-2, it can be seen that when other conditions remain unchanged, controlling the flow rate of each gas within the above range is conducive to further improving the optical properties of the optical film, the thickness uniformity of the film layer, and the interlayer bonding strength.
[0055] The difference between Example 9-10 and Example 7 is that the number of repetitions of steps S4 and S5 is different, wherein in Example 9, the number of repetitions of steps S4 and S5 is within the range of 4-5 times. Combined with the test data in Table 1-2, it can be seen that when steps S4 and S5 are repeated 4-5 times in sequence, the transmittance of the obtained optical film in the wavelength ranges of 450-530nm, 600-700nm and 1000-1200nm is more than 90%, and the optical performance of the optical film is further improved.
[0056] The difference between Example 11-12 and Example 9 is that the thickness of each layer is different. x The deposition thickness of the layer is in the range of 28-30nm, SiN x The deposition thickness of the layer is in the range of 10-12 nm, SiO x N y The deposition thickness of the layer is in the range of 140-145 nm, SiO x F y The deposition thickness of the layer is in the range of 84.5-86.5 nm. Combining the test data in Table 1-2, it can be seen that the thickness of each layer is further preferably in the above range, which is conducive to further improving the transmittance of the optical film in the wavelength ranges of 450-530 nm, 600-700 nm and 1000-1200 nm.
[0057] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A PECVD preparation process for an optical thin film, characterized in that: The following steps are involved: S1. Preheating the substrate: Preheat the double-sided polished substrate in a vacuum of 3.5*10 -4 Pa-4.0*10 -4 Pa, preheat in a chamber at 100-105°C for 10-20 min; S2, deposition of SiO x Layer: Stop evacuating the chamber, introduce SiH4 and N2O into the chamber, the flow ratio of SiH4 to N2O is 1:(1.0-1.2), the RF power is controlled to 200-250W, the reaction pressure is controlled to 20-30Pa, and the deposition thickness is 25-35nm; S3, deposition of SiN x Layer: Evacuate the chamber to 9.4*10 -3 Pa-9.8*10 -3 Pa, then stop vacuuming, introduce SiH4 and N2 into the chamber, the flow ratio of SiH4 to N2 is 1: (1.0-1.2), the RF power is controlled to 200-250W, the reaction pressure is controlled to 20-30Pa, and the deposition thickness is 10-15nm; S4, deposition of SiO x N y Layer: Evacuate the chamber to 9.4*10 -3 Pa-9.8*10 -3 Pa, then stop vacuuming, introduce SiH4, N2O and N2 into the chamber, the flow ratio of SiH4, N2O and N2 is (4-8): 1: (4-8), the RF power is controlled to 200-250W, the reaction pressure is controlled to 20-30Pa, and the deposition thickness is 135-155nm; S5. Deposition of SiO x F y Layer: Evacuate the chamber to 9.4*10 -3 Pa-9.8*10 -3 Pa, then stop vacuuming, and introduce SiH4, N2O and C2F6 into the chamber. The flow ratio of SiH4, N2O and C2F6 is (4-8): (4-8): 1, the RF power is controlled to 200-250W, the reaction pressure is controlled to 20-30Pa, and the deposition thickness is 80-90nm; S6, repeat steps S4 and S5 3-8 times in sequence; S7. Repeat steps S2 and S3 once to obtain an optical film.
2. The PECVD preparation process for an optical thin film according to claim 1, characterized in that: Deposition of SiO x N y When the layer is formed, the flow ratio of SiH4, N2O and N2 is (5-5.5):1:(4.2-4.5).
3. The PECVD preparation process for an optical thin film according to claim 1, characterized in that: Deposition of SiO x F y When the layer is formed, the flow ratio of SiH4, N2O and C2F6 is (5-5.5): (4.8-5.2):
1.
4. The PECVD process for preparing an optical thin film according to claim 1, characterized in that: In step S2, the flow rate of SiH4 is controlled to be 70-75sccm, in step S3, the flow rate of SiH4 is controlled to be 70-75sccm, in step S4, the flow rate of N2O is controlled to be 15-20sccm, and in step S5, the flow rate of C2F6 is controlled to be 15-20sccm.
5. The PECVD preparation process for an optical thin film according to claim 1, characterized in that: In step S6, steps S4 and S5 are repeated 4-5 times in sequence.
6. The PECVD process for preparing an optical thin film according to claim 1, characterized in that: The SiO x The layer was deposited with a thickness of 28-30 nm.
7. The PECVD process for preparing an optical thin film according to claim 1, characterized in that: The SiN x The layer was deposited with a thickness of 10-12 nm.
8. The PECVD process for preparing an optical thin film according to claim 1, characterized in that: The SiO x N y The deposition thickness of the layer is 140-145 nm. x F y The deposited layer thickness was 84.5-86.5 nm.
9. A PECVD process for preparing an optical thin film according to any one of claims 1 to 8, characterized in that: The substrate is any one of a polymethyl methacrylate substrate, a polycarbonate substrate and a polystyrene substrate.
10. An optical film, characterized in that: The optical film is prepared by the PECVD preparation process of any one of claims 1 to 9.
Citation Information
Patent Citations
Method for manufacturing solar cell laminated antireflective film through tubular PECVD
CN103943717A
Structured multilayer optical film with self-focusing function and production method thereof
CN110850514A
Method of manufacturing an optical reflector with semiconductor nanocrystals
US20130052772A1
